Exogenous Mitochondrial Transplantation Facilitates the Recovery of Autologous Nerve Grafting in Repairing Nerve Defects - Dongdong Li; Haolin Liu; Chaochao Li; Yanjun Guan; Xing Xiong; Ruichao He; Zhibo Jia; Lijing Liang; Jinjuan Zhao; Xinyu Miao; Yu Wang; Jiang Peng (Cell Transplantation)
Autologous nerve transplantation (ANT) remains the gold standard for treating nerve defects. However, its efficacy in nerve repair still requires improvement. Mitochondrial dysfunction resulting from nerve injury may be a significant factor limiting nerve function restoration. This study investigated the impact of supplementing exogenous mitochondria (EM) in ANT and explored its effect on the efficacy of ANT in nerve repair. SD rats were used to prepare a model of a 10 mm sciatic nerve defect repaired by ANT (Auto group) and a model of ANT supplemented with EM (Mito group). At 12 weeks post-operation, functional, neurophysiological, and histological evaluations of the target organ revealed that the Mito group exhibited significantly better outcomes compared with the Auto group, with statistically significant differences ( P < 0.05). In vitro experiments demonstrated that EM could be endocytosed by Schwann cells (SCs) and dorsal root ganglion neurons (DRGs) when co-cultured. After endocytosis by SCs, immunofluorescence staining of autophagy marker LC3II and mitochondrial marker Tomm20, as well as adenoviral fluorescence labeling of lysosomes and mitochondria, revealed that EM could promote autophagy in SCs. CCK8 and EDU assays also indicated that EM significantly promoted SCs proliferation and viability. After endocytosis by DRGs, EM could accelerate axonal growth rate. A sciatic nerve defect repair model prepared using Thy1-YFP-16 mice also revealed that EM could accelerate axonal growth in vivo , with statistically significant results ( P < 0.05). This study suggests that EM enhances autophagy in SCs, promotes SCs proliferation and viability, and increases the axonal growth rate, thereby improving the efficacy of ANT. This research provides a novel therapeutic strategy for enhancing the efficacy of ANT in nerve repair.